THÀNH PHẦN LOÀI VÀ PHÂN BỐ CỦA CÁ TRONG CÁC THỦY VỰC RỪNG ĐẶC DỤNG NA HANG, TỈNH TUYÊN QUANG - Trần, Văn Đạt (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
SPECIES COMPOSITION AND DISTRIBUTION OF FISHES IN NA HANG SPECIAL-USE FOREST, TUYEN QUANG PROVINCEResults of the surveys conducted in 2017 and 2018 show that the total number of fish species at the Na Hang special-use forest was counted at 41 species, with 34 genera and 15 families of 4 orders. Of them, the Cypriniformes order are the most abundant 22 species (53,7%). Perciformes is the most abundant of families with 6 families (40%). There is richness in number the species of Balitoridae and Gobiidae in habitats and streams have high flow rate, limestone substrata, while in the power reservoir, number the species of families Cypprinidae are recorded in large numbers and larger in size. There are three rare species which was listed in Vietnamese Red Data Book (2007): 02 species of VU level and 01 species of EN level; 03 species were listed in the IUCN Red List: 01 species of VU level and 02 species of NT level.